Klusterisasi Fitur Tanya Dokter Pada Website Alodokter Menggunakan Metode Latent Dirichlet Allocation - I Putu Fajar Tapa Mahendra; I Gusti Ngurah Anom Cahyadi Putra (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Digital advancements have change information-seeking behaviors, particularly in health inquiries for the people. The Alodokter website's